Maintenance of the Lifeboat on Board the MV Jambo X - Najwa Aulia Ramadhani; Dety Sutralinda; Ardhiana Puspitacandri; Iie Suwondo (International Journal of Science and Environment (IJSE), 2026)
Maritime accidents are still dominated by human error and suboptimal maintenance of safety equipment, making lifeboat readiness a crucial aspect of ship safety management. This study aims to analyze the lifeboat maintenance procedures on board the MV. Jambo X and evaluate their compliance with SOLAS and ISM Code provisions. The study used a qualitative descriptive approach with a single case study design. The population was all deck crew involved in lifeboat maintenance, with a purposively selected sample of the Captain, Second Officer, and Boatswain. Data were collected through semi-structured interviews, participant observation, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that lifeboat maintenance had been carried out systematically through the Safety Management System and Planned Maintenance System, with most components in good condition and ready for use. However, inconsistencies were found in operational testing and equipment placement due to operational constraints. In conclusion, the lifeboat maintenance system is generally effective and meets standards, but requires improvement in the consistency of implementation and equipment arrangement to strengthen emergency preparedness.